1973
DOI: 10.1002/pssb.2220580127
|View full text |Cite
|
Sign up to set email alerts
|

Friedel's Law in Electron Diffraction as Applied to the Study of Domain Structures in Non‐Centrosymmetrical Crystals

Abstract: BY R . SERNEELS (a), M. SNYKERS (b), P. DELAVIGNETTE (b), R. GEVERS (a, b), and S. AMELINCKX (a, b)It is shown that a strong contrast may arise in dark-field electron microscope images between two crystal parts related by an inversion operation, as a result of the violation of Friedel's law. Friedel's law is violated only in the diffracted beam and only in cases where a multiple-beam situation prevails. Moreover the excited reflections must belong to B zone which reveals the non-centrosymmetrical character of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(37 citation statements)
references
References 11 publications
0
36
0
1
Order By: Relevance
“…In order to reveal the inversion character of these domains, we have carried out multi-beam dark field experiments with reflections exhibiting the non centrosymmetric character of the crystal. Serneels et al [73] have demonstrated that phys. stat.…”
Section: Identification Of the Inversion Domainsmentioning
confidence: 99%
“…In order to reveal the inversion character of these domains, we have carried out multi-beam dark field experiments with reflections exhibiting the non centrosymmetric character of the crystal. Serneels et al [73] have demonstrated that phys. stat.…”
Section: Identification Of the Inversion Domainsmentioning
confidence: 99%
“…One of them, proposed by Serneels et al [7], is based on the violation of Friedel's law in the case when multiple diffraction conditions along a noncentrosymmetric zone axis are applied. GaN.…”
mentioning
confidence: 99%
“…In order to prove that V-defects in InN are IDs we used the criterion proposed by Serneels et al [24]. Under multiple diffraction conditions we collected pairs of dark field micrographs of the same V-like defect.…”
mentioning
confidence: 99%